2000
DOI: 10.1597/1545-1569_2000_037_0017_taucpa_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Unoperated Cleft Patient: Absence of Maxillary Teeth outside the Cleft Area

Abstract: Objective The purpose of this study was to investigate the possible absence of teeth in the postcanine region of the upper jaw of the unoperated adult cleft patient. Method The study was performed on 266 dental casts of fully unoperated adult cleft patients. The patients were divided into four groups according to the type of the cleft: unilateral cleft lip and alveolus, unilateral cleft lip and palate, bilateral cleft lip and alveolus, and bilateral cleft lip and palate. Results No absence of permanent tee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 4 publications
2
15
1
2
Order By: Relevance
“…The prevalence of tooth agenesis among cleft patients is significantly higher (45–77%; ) than among non‐cleft patients (3.2–7.6%; ). One reason for this may lie in specific surgical procedures, such as periosteoplasty or neonatal closure .…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of tooth agenesis among cleft patients is significantly higher (45–77%; ) than among non‐cleft patients (3.2–7.6%; ). One reason for this may lie in specific surgical procedures, such as periosteoplasty or neonatal closure .…”
Section: Discussionsupporting
confidence: 88%
“…It has been postulated that specific surgical procedures performed during tooth formation, such as palatoplasty, can influence tooth bud growth and maturation, thus playing a role in maxillary tooth agenesis . Supporting this hypothesis, a lower prevalence of maxillary tooth agenesis has been found in unoperated individuals with clefts, but the increased prevalence of mandibular tooth agenesis is clearly independent from this hypothesis. Moreover, if this hypothesis were true, prevalence of maxillary permanent tooth agenesis would be similar in repaired isolated cleft palates and cleft palates in those with ns‐RS, but studies find that prevalence rates of permanent tooth agenesis are significantly higher in cleft palates associated with ns‐RS than in isolated cleft palates .…”
Section: Discussionmentioning
confidence: 99%
“…Three main factors might contribute to the increased prevalence of tooth agenesis in the BCLP patients. First, it has been hypothesized that specific surgical procedures, such as early periosteoplasty (21) or neonatal closure of the hard palate (22, 23), might influence tooth formation because a lower prevalence of tooth agenesis was found in non‐operated individuals with clefts (24). However, other studies have reported that surgical interventions do not seem to affect tooth agenesis (17).…”
Section: Discussionmentioning
confidence: 99%